Season of Infamy : A Diary of War and Occupation, 1939-1945 - Rist, Charles, 1874-1955 (Book collections on Project MUSE., 2016)
"A valuable account of what one significant and perceptive Frenchman experienced during the protracted disgrace of France as a vassal state of Nazi Germany."--Publishers Weekly In 1939, the 65-year-old French political economist Charles Rist was serving as advisor to the French government and consultant to the international banking and business world. As France anxiously awaited a German invasion, Rist traveled to America to negotiate embargo policy. Days after his return to Paris, the German offensive began and with it the infamous season of occupation. Retreating to his villa in Versailles, Rist turned his energies to the welfare of those closest to him, while in his diary he began to observe the unfolding of the war. Here the deeply learned Rist investigates the causes of the disaster and reflects on his country's fate, placing the behavior of the "people" and the "elite" in historical perspective. Though well-connected, Rist and his family and friends were not exempt from the perils and tragedies of war, as the diary makes clear. Season of Infamy presents a distinctive, closely-observed view of life in France under the occupation.